Ciri Makroskopis Fosil Kayu dari Tiga Desa di Kalimantan Timur - Nani Husien; Mia Maulida; Muhammad Nur Hidayat; Febrian; Erwin; Agus Sulityo Budi; Sujiman Kasnadi (The Ethnobiological Society of Indonesia, 2021)
Natural resources in East Kalimantan are not only in the form of forests with various types of plants, but the resources also reserve various wood fossils that have lived in the past. Until now, the types of wood fossils are almost unknown. Fossil wood should be a historical asset that needs to be preserved and protected. In addition to being evidence of prehistoric times, it can also be used as material for studying plants in the past. This study was a preliminary study that aimed to identify the macroscopic attributes of wood fossils found in three villages in the Kutai Kertanegara regency, East Kalimantan. The method used was the macroscopic preparation method of fossil samples with carborundum powder. Macroscopic observations indicated that the wood fossils found in the three locations have different macrostructures, varied in color: black, brown, red, and a mixture of several colors. In the transverse section of the three samples of wood fossils, they showed the presence of pore cells (vessels) and a narrow to relatively wide rays parenchyma cell line, which indicated that the wood fossils from these three villages were broad-leaved (Hardwood). The results of the calculation of the specific gravity of the wood fossil found ranged from 2.3 to 5.5, with a hardness value between 4 and 6 on the Mohs scale.